2018
DOI: 10.1093/jac/dkx479
|View full text |Cite
|
Sign up to set email alerts
|

TGF-β-mediated NADPH oxidase 4-dependent oxidative stress promotes colistin-induced acute kidney injury

Abstract: Collectively, these findings identify Nox4 as a key source of reactive oxygen species responsible for kidney injury in colistin-induced nephrotoxicity and highlight a novel potential way to treat drug-related nephrotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 46 publications
1
42
0
Order By: Relevance
“…Accumulated studies have demonstrated that TGF-β1 stimulated the production of ROS in various cell types, which in turn activated TGF-β and mediated many fibrogenic effects. Some studies have shown that TGF-β/Smad signaling plays a vital role in oxidative stress [23]. We investigated the relationship between TGF-β/Smad signaling and oxidative stress in PMCs; however, LY2109761 treatment did not decrease ROS production, indicating that TGF-β1-induced ROS in HPMCs does not depend on TGF-β/Smad signaling.…”
Section: Discussionmentioning
confidence: 86%
“…Accumulated studies have demonstrated that TGF-β1 stimulated the production of ROS in various cell types, which in turn activated TGF-β and mediated many fibrogenic effects. Some studies have shown that TGF-β/Smad signaling plays a vital role in oxidative stress [23]. We investigated the relationship between TGF-β/Smad signaling and oxidative stress in PMCs; however, LY2109761 treatment did not decrease ROS production, indicating that TGF-β1-induced ROS in HPMCs does not depend on TGF-β/Smad signaling.…”
Section: Discussionmentioning
confidence: 86%
“…Further support for this claim came from studies where PPP increased the expression of typical TGF-β target genes, such as connective tissue growth factor (CTGF), in tendinopathic cells [37] and hypertrophic scar dermal fibroblasts [38], considering that the primary effects of TGF-β are at least partially mediated via this growth factor [39]. Similar to CTGF, it is IL11 and NOX4 that are regulated by PPP lysates that mediate the effects of TGF-β on cardiovascular and liver fibrosis [29,30], and acute kidney injury and pulmonary fibrosis [31,34], respectively. Thus, IL11 and NOX4 are not only sensitive TGF-β target genes in vitro as they mediate at least part of the TGF-β activity in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of heating on the activity of TGF-β is biphasic-TGF-β, because of its binding to latent TGF-β binding proteins, gaining activity by heating [26], while temperatures above 90 • C result in thermal denaturation of TGF-β [27]. Considering that TGF-β is a pleiotropic growth factor that is critically involved in wound healing and bone regeneration [28], and since some of TGF-β effects in vivo are mediated via IL11 [29,30] and NOX4 [31], bioassays based on the expression of these two sensitive target genes are suitable to measure TGF-β activity in PRF.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, several evidences suggest that NADPH oxidative (Nox) is the dominant source of ROS in the kidney. [26][27][28] Therefore, we analyzed the expression of Nox in NRK-52E cells transfected with shSelT by RNA-seq. As shown in Figure 6A, SelT silencing upregulated the expression of Nox4.…”
Section: Nox1/4 Inhibitor Attenuates Ros Production and Cell Apoptomentioning
confidence: 99%